“I hate coke”: an nethnographic analysis about speech anti-brand of the virtual community on orkut - Abdalla, Márcio Moutinho (2011)
It is evident broad organizational concerns regarding the management and maintenance of their brands. Retaliatory and repudiation action against product and services brands are shown as imposing barriers to be implemented by organizations. Thus, this study aims to deepen understanding of the subject by analyzing the speech of members of the virtual community antibrand "eu odeio coca-cola (I hate Coke)" in Orkut social network, besides seeking the motivations that led these members to express their opinions. As research procedures, drew on an exploratory analysis by conducting a search netnography, which led the researchers to immerse themselves in the community for a period of one year, featuring a longitudinal study. For the analysis of information, was employed discourse analysis, which enabled the categorization of the motivations for community members to express their opinions. As a result, we found six categories of behavior, which were (1) negative experience of consumption, (2) brand association with health/aesthetics problems, (3) presumed use of illicit material in the product, (4) concern with the effects of globalization, and (5) religious foundation, and another topic for (6) the defense of the target mark. Stands out, however the prevalence of category “1” and “4”. It was considered that the anti-consumer present in the virtual community associate the target brand as a symbol of imperialism and hegemony of globalization, triggering factor for much of the criticism.